2002
DOI: 10.1097/00124784-200211000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis Contact Investigation Policies, Practices, and Challenges in 11 U.S. Communities

Abstract: To describe the policies and procedures used by 11 urban tuberculosis control programs to conduct contact investigations, written policies were reviewed and semi-structured interviews were conducted with program managers and staff. Qualitative analysis showed that contact investigation policies and procedures vary widely. Most policies address risk factor assessment and contact prioritization; however, none of the policies provide comprehensive guidance for the entire process. Staffing patterns vary, but, over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 13 publications
2
17
0
Order By: Relevance
“…Few studies, however, provided data regarding these indicators. Wilce et al 113 highlighted the variability in accuracy of information recorded and the need for improvement in this area. Only one paper 97 referred to awareness raising as an outcome from an investigation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Few studies, however, provided data regarding these indicators. Wilce et al 113 highlighted the variability in accuracy of information recorded and the need for improvement in this area. Only one paper 97 referred to awareness raising as an outcome from an investigation.…”
Section: Discussionmentioning
confidence: 99%
“…105 Others concluded that the screening of casual contacts was not cost-effective in low incidence areas, 38 should be carried out only for smear-positive respiratory index cases 102 or only for highly infectious cases, 33 or that there should be only limited screening of casual contacts. 87 The authors of one study 113 found that the 39 defined a close contact as someone having < 4 hours' exposure indoors or in a confined space, and a casual contact as someone with exposure other than close. Another study 42 defined people who spent an estimated total of at least 40-100 hours with the index cases in the 3 months prior to diagnosis or during the infectious period as 'close contacts', and those who shared the same front door as the index case as 'household contacts'.…”
Section: Individual-focused Strategiesmentioning
confidence: 99%
See 3 more Smart Citations